2021
DOI: 10.3390/v13112251
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hamster Natural Transmission Model of SARS-CoV-2 Infection

Abstract: The global pandemic of coronavirus disease (COVID-19) caused by infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has led to an international thrust to study pathogenesis and evaluate interventions. Experimental infection of hamsters and the resulting respiratory disease is one of the preferred animal models since clinical signs of disease and virus shedding are similar to more severe cases of human COVID-19. The main route of challenge has been direct inoculation of the virus via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 24 publications
1
44
0
1
Order By: Relevance
“…In agreement with previous studies (Dowall et al, 2021; Gruber et al, 2020; Nouailles et al, 2021), SARS-CoV-2 infected lung tissue showed pulmonary lesions consisting of broncho-interstitial pneumonia extending into the alveoli and multifocal areas of consolidation, consistent with inflammatory cell infiltration and oedema (Fig.4A, Supplementary Fig.5) . Digital image analysis showed that FG-4592 treatment did not alter the severity of lung histopathology (Fig.4C) .…”
Section: Resultssupporting
confidence: 92%
“…In agreement with previous studies (Dowall et al, 2021; Gruber et al, 2020; Nouailles et al, 2021), SARS-CoV-2 infected lung tissue showed pulmonary lesions consisting of broncho-interstitial pneumonia extending into the alveoli and multifocal areas of consolidation, consistent with inflammatory cell infiltration and oedema (Fig.4A, Supplementary Fig.5) . Digital image analysis showed that FG-4592 treatment did not alter the severity of lung histopathology (Fig.4C) .…”
Section: Resultssupporting
confidence: 92%
“…Similarly, most animal studies exploring SARS-CoV-2 have challenged animals intra-nasally, intra-ocularly, or intra-orally, with few delivered by the aerosol route [ 14 , 15 , 16 , 17 , 18 ]. Only one recent study examined natural transmission between intra-nasally infected hamsters to naïve animals [ 47 ]. Our study sought to characterise the MMAD and viability of SARS-CoV-2 aerosols generated with different relative humidities from six nebulisers.…”
Section: Discussionmentioning
confidence: 99%
“…Future work employing different aerosol capture methods, such as the Goldberg drum or spider microthreads, could explore decay rates over longer time periods, of virus in different temperature and relative humidities, and also incorporate electron microscopy images of the virus to determine physical effects of nebulisation compared to those observed in sputum. Future work may also involve comparison of natural transmission in animal models [ 47 ] to those animals infected via nebuliser-generated aerosols; such work may aid elucidation of the particle sizes and concentrations generated by intra-nasally infected animals, in aerosol infection models.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Only one recent study examined natural transmission between intra-nasally infected hamsters to naïve animals. [47] Our study sought to characterise the MMAD and viability of SARS-CoV-2 aerosols generated with different relative humidities from six nebulisers. To date, no other work has compared nebulisation effects on SARS-CoV-2 across such devices; nor attempted to characterise by size-fractionation, viable SARS-CoV-2 virus particles, using these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Future work employing different aerosol capture methods, such as the Goldberg drum or spider microthreads, could explore decay rates of virus in different temperature and relative humidities, and also incorporate electron microscopy images of the virus to determine physical effects of nebulisation compared to those observed in sputum. Future work may also involve comparison of natural transmission in animal models [47] to those animals infected via nebuliser-generated aerosols; such work may aid elucidation of the particle sizes and concentrations generated by intra-nasally infected animals, in aerosol infection models.…”
Section: Discussionmentioning
confidence: 99%